National Identity in International Relations: Between Constructivism and Post-Structuralism (Czech Journal of International Relations, 2017)
The article interprets the role of national identity in contemporary international relations scholarship. It distinguishes two main approaches – the social constructivist and post-structural approaches – and shows their deficiencies. To overcome them, it offers a third way to approach identity that builds on a pragmatic combination of these two schools. It proposes grasping identity according to the extent of its sedimentation. At the lowest level of sedimentation, identity entrepreneurs fight for their visions of identity. The middle level is where more concrete demarcations are made. The most sedimented identities take on the form of a culture as defined by social constructivists. The identities in all the layers interact with each other, both positively (less sedimented layers accelerate changes in more sedimented layers) and negatively (deeper identities inhibit changes in lower levels).
Keywords: identity; constructivism; post-structuralism; edimentation; otherness; pragmatism; emotions